2012
DOI: 10.1101/lm.021311.110
|View full text |Cite
|
Sign up to set email alerts
|

Infantile amnesia: A neurogenic hypothesis

Abstract: In the late 19th Century, Sigmund Freud described the phenomenon in which people are unable to recall events from early childhood as infantile amnesia. Although universally observed, infantile amnesia is a paradox; adults have surprisingly few memories of early childhood despite the seemingly exuberant learning capacity of young children. How can these findings be reconciled? The mechanisms underlying this form of amnesia are the subject of much debate. Psychological/cognitive theories assert that the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 155 publications
(206 reference statements)
2
102
0
1
Order By: Relevance
“…Related to longer-term memory processing Josselyn and Frankland (2012) have proposed that neurogenesis may actively destabilize memories and hence promote forgetting. The authors cite the inverse correlation, through development, between rates of hippocampal neurogenesis and the ability to lay down longterm memories, and have found that promoting AHN postlearning diminishes the retrieval of previously established memories (Frankland et al 2013).…”
Section: Contextual and Spatial Memorymentioning
confidence: 99%
“…Related to longer-term memory processing Josselyn and Frankland (2012) have proposed that neurogenesis may actively destabilize memories and hence promote forgetting. The authors cite the inverse correlation, through development, between rates of hippocampal neurogenesis and the ability to lay down longterm memories, and have found that promoting AHN postlearning diminishes the retrieval of previously established memories (Frankland et al 2013).…”
Section: Contextual and Spatial Memorymentioning
confidence: 99%
“…As one example, in a series of experiments Rovee-Collier and colleagues have shown that retention in human infants trained on an operant procedure (e.g., the mobile conjugate reinforcement task, where the infant learns to kick one leg to produce movement in an overhanging mobile, or the train task, where the infant learns to press a manipulandum to cause an electric train to move) increases monotonically with age over the first years of life (for review, Although we have long been aware of the robust phenomenon of infantile amnesia, in the past 50 years there have been surprisingly few advances in our understanding of the physiological bases of this rapid forgetting. However, several recent papers have suggested potential molecular and structural mechanisms that could be involved in infantile amnesia (e.g., Josselyn and Frankland 2012;Frankland et al 2013;Callaghan et al 2014). These potential mechanisms are largely derived from recent studies on the molecular and structural bases of memory in adults.…”
Section: Infantile Amnesiamentioning
confidence: 99%
“…However, several recent papers have suggested potential molecular and structural mechanisms that could be involved in infantile amnesia (e.g., Josselyn and Frankland 2012;Frankland et al 2013;Callaghan et al 2014). These potential mechanisms are largely derived from recent studies on the molecular and structural bases of memory in adults.…”
mentioning
confidence: 99%
“…Empirical studies have shown that events, including traumatic ones that occur before the age of 2-3 years are unlikely to be available for conscious verbal recall (Cordon et al 2004;Newcombe et al 2007;Simcock and Hayne 2002). This phenomenon is usually referred to as "infantile amnesia" and has been validated by over a century of empirical research (Bauer 2007;Josselyn and Frankland 2012). By the age of three, however, children's recall of stressful events can be consistent and robust (Peterson and Warren 2009), and they are able to recall stressful negative events over time, as well as reporting new correct information (Baugerud et al 2014;Lamb et al 2011).…”
Section: Children's Memory Developmentmentioning
confidence: 99%